1989
DOI: 10.1507/endocrj1954.36.155
|View full text |Cite
|
Sign up to set email alerts
|

Two-Site Immunoradiometric Assay for Adrenocorticotrophin: A Cautionary Study about the Reactivity to Its Precursor Molecules.

Abstract: The specificity of a "two-site" immunoradiometric assay (IRMA) has been reevaluated by examining its ability to detect heterogeneous adrenocorticotrophin-like immunoreactivity (ACTH-LI) separated by gel column chromatography. Plasma samples from patients with Addison's disease, Nelson's syndrome and ectopic ACTH syndrome and tissue extract of human anterior pituitary were subjected to ACTH-IRMA and the levels of ACTH-LI were compared with those measured by conventional ACTH-radioimmunoassay (RIA). The level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Hodgkinson et al (171) was found not to detect the "big ACTH" produced by tumors (139). Similarly, ACTH fragments not detected in the immunoradiometric assays can cause problems (317).…”
Section: B Immunoassays For Acthmentioning
confidence: 98%
“…Hodgkinson et al (171) was found not to detect the "big ACTH" produced by tumors (139). Similarly, ACTH fragments not detected in the immunoradiometric assays can cause problems (317).…”
Section: B Immunoassays For Acthmentioning
confidence: 98%
“…LIF acts through a specific receptor subunit forming a heterodimeric complex with gpl3O (9)(10), a signal transduction molecule shared with oncostatin M (OSM) and interleukin 6. Corticotrophin-releasing hormone (CRH) is an important regulator of the hypothalamic-pituitary-adrenal axis during development and also in response to stress (11)(12). This hypothalamic peptide induces adenylate cyclase activity and stimulates pro-opiomelanocortin (POMC) gene transcription (13) and adrenocorticotrophin (ACTH) release (14), and may be mitogenic for pituitary corticotroph cells in vivo (15) and in vitro (16).…”
mentioning
confidence: 99%